(untitled) (International Journal of Financial, Administrative and Economic Sciences, 2026)
This study investigates the impact of electronic human resource management (e-HRM) practices—namely e-recruitment, e-training, e-performance appraisal, and e-compensation systems—on institutional performance, in terms of financial and administrative dimensions, at the headquarters of the Republic Bank in Libya. A descriptive–analytical approach was adopted, and data were collected through a questionnaire administered to a sample of employees and managers. Statistical analysis was conducted using SPSS. The findings reveal a high level of e-HRM implementation at the bank and a statistically significant positive effect on overall institutional performance, with the study model explaining 50.6% of the variance. The impact was more pronounced on financial performance than on administrative performance. The study recommends updating organizational structures, increasing investment in digital technologies and artificial intelligence applications, and expanding electronic training platforms to enhance human resource efficiency and institutional performance.